Development of E-Student Worksheet Based on Problem Based Learning Assisted by Augmented Reality in Science Learning to Improve Digital Literacy Skills - Muizzatissalmi, Hadyatul; Ramdani, Agus; Setiadi, Dadi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Learning in digital era still faces obstacle in the form of low student`s digital literacy skill. This study aims to develop valid, practical, and effective E-LKPD based on PBL assisted by AR to improve digital literacy skills. This type of research is R&D with a research method adapting 4D development model. The novelty of this research is the combination of E-LKPD with the PBL model assisted by 3D media from Assemblr combined using Canva to increase student interest in learning process which is then adjusted to digital literacy indicators to improve student`s digital literacy skills. The subjects of this study were 105 students at SMPN 1 Batukliang. Data analysis for validity used the CVI test from the validity results using instruments validated by 3 experts. Practicality data was seen from implementation of the learning process, teacher responses, and student responses. Effectiveness data was analyzed using N-Gain and Mann Whitney Tests from the results of the student`s pretest and posttest. The results of the validity showed a CVI value of 1.00 (valid). The implementation of learning showed an average value of 92% (very practical); teacher response 82% (very practical); and student response 91% (very practical). Meanwhile, the effectiveness received an N-Gain value of 0.70 (effective), the significance value of the Mann Whitney digital literacy test was 0.012, which means there is an influence of E-LKPD to improve students' digital literacy skills. Based on the data obtained, this AR-assisted PBL-based E-LKPD is valid, practical, and effective for use in the learning process.